Pengembangan Media Diorama Materi Metamorfosis Kupu-Kupu Terhadap Keterampilan Berpikir Kreatif Di Sekolah Dasar - Isnaini Shavira; Aan Widiyono (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study is motivated by the dominant use of conventional teaching methods, which makes butterfly metamorphosis material difficult for students to understand and results in low creative thinking skills. The purpose of this study is to develop a diorama learning media on butterfly metamorphosis and to examine its feasibility and effectiveness in improving elementary school students' creative thinking skills. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects were 34 third-grade students of SDN 1 Pengkol Jepara. Data collection techniques included interviews, expert validation questionnaires, student responses, and pretest-posttest. The results showed that the diorama media was categorized as highly feasible by media experts (average score of 9.6) and feasible to highly feasible by material experts. Student responses also indicated a very feasible category. Effectiveness testing showed an increase in creative thinking skills with an average score of 80.5. The data were normally distributed and homogeneous, and the paired sample t-test result (0.000) indicated a significant positive difference. Therefore, the developed diorama media is proven effective in enhancing students' creative thinking skills.